Activity of florfenicol for Actinobacillus pleuropneumoniae and Pasteurella multocida using standardised versus non-standardised methodology. (December 2016) - Dorey, L.; Hobson, S.; Lees, P.
Highlights: Pasteurella multocida and Actinobacillus pleuropneumoniae are bacterial pathogens of pigs. The pharmacodynamics of florfenicol for P. multocida and A. pleuropneumoniae were investigated. Minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) were determined. Mutant prevention concentrations (MPCs) and time–kill curves were determined. Significant differences were obtained for these potency indices between pig serum and artificial broths. Abstract: Four indices of antimicrobial potency were determined for florfenicol and the pig pneumonia pathogens, Actinobacillus pleuropneumoniae and Pasteurella multocida . Minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), mutant prevention concentration (MPC) and time–kill curves were determined in two matrices, broth and pig serum. Five overlapping sets of two-fold dilutions were used to increase accuracy of the measurements. MIC and MBC serum:broth ratios for A. pleuropneumoniae were 0.96:1 and 1.07:1, respectively, and corresponding values for P. multocida were 0.72:1 and 0.50:1. The percentage binding of florfenicol to serum protein was 65.4%, and fraction unbound (fu) serum MICs were significantly lower, by 2.71-fold and 3.82-fold, respectively, than predicted for free serum concentrations for A. pleuropneumoniae and P. multocida . Similar culture medium differences were obtained for MBC and MPC. MICs in serum and broth were increased significantly and progressively for high, medium and low initial inoculum counts. Serum MPC:MIC ratios for A. pleuropneumoniae and P. multocida were 12.5:1 and 13.6:1, respectively; ratios for broth were similar. The killing action of florfenicol had the characteristics of concentration dependency for both species in both growth media. These data indicate the value of using a biological medium, when determining microbiological potency indices, to predict dosage for clinical use.